2012
DOI: 10.1016/j.cmet.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Rescues SIRT1-Dependent Adult Stem Cell Decline and Alleviates Progeroid Features in Laminopathy-Based Progeria

Abstract: Abnormal splicing of LMNA gene or aberrant processing of prelamin A results in progeroid syndrome. Here we show that lamin A interacts with and activates SIRT1. SIRT1 exhibits reduced association with nuclear matrix (NM) and decreased deacetylase activity in the presence of progerin or prelamin A, leading to rapid depletion of adult stem cells (ASCs) in Zmpste24(-/-) mice. Resveratrol enhances the binding between SIRT1 and A-type lamins to increases its deacetylase activity. Resveratrol treatment rescues ASC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(154 citation statements)
references
References 68 publications
2
149
2
1
Order By: Relevance
“…This is in agreement with several previous reports (Borra et al 2005;Kaeberlein et al 2005;Beher et al 2009;Pacholec et al 2010;Liu et al 2012) and contrasts with some others (Dai et al 2010;Hubbard et al 2013). Significantly, the two native peptides used in our experiments all have an aromatic residue at the +1 position, and the PGC-1α peptide also contains an additional aromatic residue at the +6 position, which has been suggested to further stimulation of SIRT1 activity by STACs (Hubbard et al 2013).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…This is in agreement with several previous reports (Borra et al 2005;Kaeberlein et al 2005;Beher et al 2009;Pacholec et al 2010;Liu et al 2012) and contrasts with some others (Dai et al 2010;Hubbard et al 2013). Significantly, the two native peptides used in our experiments all have an aromatic residue at the +1 position, and the PGC-1α peptide also contains an additional aromatic residue at the +6 position, which has been suggested to further stimulation of SIRT1 activity by STACs (Hubbard et al 2013).…”
Section: Discussioncontrasting
confidence: 49%
“…However, it is not unprecedented that an NTD of sirtuin harbors an allosteric activation mechanism toward native substrates. For example, binding of Sir4, principally through the NTD of Sir2, stimulates deacetylation of H4K16 by Sir2 (Tanny et al 2004;Hsu et al 2013), and binding by AROS and Lamin A, suggested via the NTD of SIRT1, potentiates the activity of SIRT1 toward p53 (Kim et al 2007;Liu et al 2012). Therefore, it is possible that, by modeling the protein-protein interaction effect with small molecules, allosteric activation of SIRT1 activation may be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HDAC2 has been shown to suppress p21 expression in human hepatocellular carcinoma via its binding to an Sp1‐binding site (Noh et al, 2011). On the other hand, it has been demonstrated that lamin A/C establishes direct interactions with histone deacetylases including SIRT1 (Cenni et al, 2014; Liu et al, 2012), SIRT6 (Ghosh, Liu, Wang, Hao, & Zhou, 2015), and HDAC1 (Kubben et al, 2016), while lamin partners at the nuclear envelope such as emerin, BAF, and LAP2beta interact with HDAC3 (Demmerle, Koch, & Holaska, 2013) or HDAC2 (Tsai et al, 2015). Moreover, lamin A/C has been demonstrated to bind gene promoters or neighboring domains and this binding has been linked to distinct transcriptional outcomes (Lee, Welton, Smith, & Kennedy, 2009; Lund & Collas, 2013; Mattout et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this regulatory pathway may be altered in human progeria and should be assessed in progeroid mouse models. In one such model, Zmpste24 −/− mice, a model for Hutchinson-Gilford progeria associated with mutations in A-type lamins, loss of SIRT1 function has already been noted in MSC populations [11]. SIRT6 was not assessed in that study; however, another recent study showed that A-type lamins are required for SIRT6 activation and support SIRT6-mediated DNA repair [12].…”
mentioning
confidence: 92%